A modular and adjustable ptosis crutch as a non-surgical solution to elevating the upper eyelid of myasthenia gravis patients - Findlay, Megan (Division of Biomedical Engineering, 2017)
Myasthenia Gravis (MG) is a treatable autoimmune disorder that affects the neuromuscular junction. MG is characterised by fatigable muscle weakness of voluntary skeletal muscles with the most commonly affected muscles being the eye and facial muscles. Patients of African genetic ancestry, particularly juveniles, are more likely to develop ocular muscle complications of MG compared to their European counterparts. MG ophthalmoplegic complications include persistent difficulty with moving the eyes and blepharoptosis, despite treatment. Blepharoptosis, or ptosis, describes the condition of a lowered upper eyelid(s), beyond its normal anatomic position. Surgical correction of ptosis is often contraindicated in MG patients with severe weakness of the muscles involved in eye closure and in patients with active disease. In these cases, a non-surgical solution to elevating the ptotic eyelid above the visual axis is required. Objective: To design a patient specific, modular and low cost ptosis crutch to elevate the eyelid(s) of myasthenia gravis patients. The ptosis crutch should be low cost, modular and adjustable in nature. Method: 16 MG patients (42 ± 23 years) volunteered to participate in the pre-design phase of the project. Initial eye measurements of each participant were taken using photographic measurement. A bottomup approach was followed for the design of the ptosis crutch. 3D CAD models of the modular ptosis crutch were created in SolidWorks, according to the measured dimensions and the predefined design parameters. The ptosis crutch was prototyped using 3D printing. Eightyseven design failures were observed before the final design was realised. A design feedback loop lead to the discovery of a device that satisfied the specified requirements. The final ptosis crutch was tested, in the clinical setting, on 12 MG patients (43 ± 24 years). Results: The ptosis crutch was designed to fit onto the superior border of the spectacle frame. The ptosis crutch is adjustable along the x- axis to cater for the inter-individual variability of globe protrusion. The crutch bar is adjusted along the z-axis and elevated the ptotic eyelid by 1.96mm (±1.11mm). All of the participants indicated that they would be interested in using the ptosis crutch on a long-term basis. Conclusion: The immediate feedback on the ptosis crutch from the MG patients has shown a positive outcome for the device. Future work will include obtaining long term feedback on the ptosis crutch from all of the users as well as investigating manufacturing methods using materials with increased durability.